Estimasi Cadangan Karbon Pada Tumbuhan Bawah dan Serasah Di Hutan Pendidikan dan Penelitian Fakultas Kehutanan Universitas Mulawarman Samarinda - Wahjuni Hartati; Ali Suhardiman; Triyono Sudarmadji; Eko Adi Sulistiyo (Fakultas Kehutanan Universitas Mulawarman, 2021)
Three slopes of 100 m long are defined in young secondary forest with gentle and slightly steep slopes. In each part of the slope, we built 1 (one) PUP of 20m x 20m which is consisted of 3 (three) Sub PUPs of 10m x 10m to represent the density of sparse, medium, and dense understorey and 1m x 1m of sub-PUPs for litter harvesting. In 18 (eighteen) PUPs, each 54 (fifty-four) Sub PUPs and Sub sub PUPs, were made in this study. The HPFU area is dominated by young secondary forest coverage with gentle and slightly steep slopes. The C reserves of the herbaceous understorey are more significant than that of woody plants. C reserves of all components studied in the gently sloping area are larger than the steep ones. The largest C reserves are found in leaf litter for all slope positions except for a slightly steep lower slope. The largest C reserves is found in finer litter. The total C reserves of understorey and young secondary forest organic litter in HPFU 933.4 tons and 95.9 percent are stored in a litter.